Laser-Actuated Multi-Fingered Hand for Dexterous Manipulation of Micro-Objects - Quang Minh Ta; Gulam Dastagir Khan; Xiang Li; Chien Chern Cheah (IEEE Access, 2023)
Dexterous robotic manipulation refers to the coordination of multiple fingers or manipulators to grasp and manipulate a target object. In past decades, various achievements have been established in dexterous robotic manipulation in the physical world. However, such dexterous ability is rarely found in nano/micro manipulation, which is mainly due to the difficulty in developing actuators and sensors at a nano/micro-scale, as well as the dependence on the physical properties of objects. As a result, only limited and relatively simple micro-manipulation tasks such as pushing and picking have been realized so far. Here, we demonstrate a platform to achieve dexterous manipulation in the micro-world by developing a micro multi-fingered hand that is actuated by optical traps. The system consists of several micro laser-actuated fingers which are coordinated to function as a robotic micro-hand. Each micro-finger is configured with three degrees of freedom in a 2-dimensional space, and a system composed of coordinated micro-fingers can then be utilized for grasping, rotating, moving, and even levering and rolling of objects in micron scale. Thus, the proposed approach in this paper establishes a foundation in achieving dexterous robotic manipulation of objects at micron scale through the coordination of multiple micro-fingers.